TRIM5α and TRIMCyp form apparent hexamers and their multimeric state is not affected by exposure to restriction-sensitive viruses or by treatment with pharmacological inhibitors - Nepveu-Traversy, Marie-Édith (BioMed Central, 2009)
Proteins of the TRIM5 family, such as TRIM5α and the related TRIMCyp, are cytoplasmic factors that can inhibit incoming retroviruses. This type of restriction requires a direct interaction between TRIM5 proteins and capsid proteins that are part of mature, intact retroviral cores. In such cores, capsids are arranged as hexameric units. Multiple lines of evidence imply that TRIM5 proteins themselves interact with retroviral cores as multimers. Accordingly, stabilization by crosslinking agents has revealed that TRIM5α and TRIMCyp are present as trimers in mammalian cells. We report here that TRIM5 proteins seem to form dimers, trimers, hexamers and multimers of higher complexity in mammalian cells. The hexameric form in particular seems to be the most abundant multimer. Multimerization did not involve disulfide bridges and was not affected by infection with restriction-sensitive viruses or by treatment with the known TRIM5 inhibitors arsenic trioxide, MG132 and cyclosporine A. We conclude that TRIM5 multimerization results from more than one protein-protein interface and that it is seemingly not triggered by contact with retroviral cores.